2012
DOI: 10.1038/ejhg.2011.271
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel in-frame de novo mutation in SPTAN1 in intellectual disability and pontocerebellar atrophy

Abstract: Heterozygous in-frame mutations (p.E2207del and p.R2308_M2309dup) in the a-II subunit of spectrin (SPTAN1) were recently identified in two patients with intellectual disability (ID), infantile spasms (IS), hypomyelination, and brain atrophy. These mutations affected the C-terminal domain of the protein, which contains the nucleation site of the a/b spectrin heterodimer. By screening SPTAN1 in 95 patients with idiopathic ID, we found a de novo in-frame mutation (p.Q2202del) in the same C-terminal domain in a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…Furthermore, in primary neuronal cultures, the p.Q2202 del mutation showed a similar aggregation profile, but in a lower proportion of cells. 23 These expression data suggest that the degree of aggregation involving α-II/β-II and α-II/β-III spectrin heterodimers could correlate with the severity of clinical symptoms. It is also notable that two patients (subjects 2 and 4) with a duplication mutation in the last spectrin repeat passed away early in childhood.…”
Section: Role Of Spectrinsmentioning
confidence: 96%
See 4 more Smart Citations
“…Furthermore, in primary neuronal cultures, the p.Q2202 del mutation showed a similar aggregation profile, but in a lower proportion of cells. 23 These expression data suggest that the degree of aggregation involving α-II/β-II and α-II/β-III spectrin heterodimers could correlate with the severity of clinical symptoms. It is also notable that two patients (subjects 2 and 4) with a duplication mutation in the last spectrin repeat passed away early in childhood.…”
Section: Role Of Spectrinsmentioning
confidence: 96%
“…A total of seven epileptic patients with four different in-frame SPTAN1 mutations have been identified to date. Interestingly, Hamdan et al 23 also reported a de novo p.R566P mutation in a patient with mild nonsyndromic ID without epilepsy. The pathological significance of this missense mutation is unclear because the patient's sister, who has similar clinical features, does not carry the SPTAN1 mutation.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations